Association of rs3755319 and rs4148325 of the UGT1A1 gene, rs2328136 of the NUP153-AS gene, and rs16928809 of the SLC22A18 gene with benign unconjugated hyperbilirubinemia - Anastasiya A. Ivanova; Natalia E. Apartseva; Anastasiia P. Kashirina; Elena G. Nemcova; Julija V. Ivanova; Margarita V. Kruchinina; Svetlana A. Kurilovich; Vladimir N. Maksimov (Alʹmanah Kliničeskoj Mediciny)
Background: Benign unconjugated hyperbilirubinemia, also known as Gilbert's syndrome, is a common in the population moderate increase in total and unconjugated bilirubin concentrations in individuals without liver disease or hemolysis.